2016
DOI: 10.1259/bjr.20150971
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two MR grading systems for correlation between grade of cervical neural foraminal stenosis and clinical manifestations

Abstract: Objective: To compare the reliability of two recently reported MR grading systems of cervical neural foraminal stenosis (CNFS) and their correlation with clinical manifestations. Methods: We evaluated 188 patients (male : female 5 80 : 108; mean age of 41 years) who visited our institution and underwent oblique sagittal MRI of the cervical spine. Two radiologists evaluated the MRI findings for the presence and grade of CNFS at the narrowest point, with the grading systems (Park, Kim and mKim systems) suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…CFS is caused by the narrowing of cervical nerve roots at the entrance of cervical foramen and is seen commonly. Significant narrowing of the cervical foramen may present as a sharp arm or neck pain, paresthesia, numbness or tingling sensation with or without symptoms spreading to the distal portion of the upper extremities 2,5. In order to exclude the possibility of other diseases and to determine appropriate treatment, an accurate CMRI diagnosis of CFS is essential 3,16.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CFS is caused by the narrowing of cervical nerve roots at the entrance of cervical foramen and is seen commonly. Significant narrowing of the cervical foramen may present as a sharp arm or neck pain, paresthesia, numbness or tingling sensation with or without symptoms spreading to the distal portion of the upper extremities 2,5. In order to exclude the possibility of other diseases and to determine appropriate treatment, an accurate CMRI diagnosis of CFS is essential 3,16.…”
Section: Discussionmentioning
confidence: 99%
“…Compression or irritation of the cervical nerve root as it travels through a neural foramen causes cervical radiculopathy 24. Motor symptoms such as weakness may sometimes accompany sensory symptoms in aggravated narrowing 57. Cervical spine magnetic resonance imaging (CMRI) is the most sensitive technique for detecting early morphological changes in the cervical spine 3,8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Lee et al 14 demonstrated that the degree of CNFS was relatively highly correlated with clinical manifestation. However, Kim et al 6 retrospectively assessed pain intensity and treatment outcomes of CTEB based on the degree of CNFS.…”
Section: Introductionmentioning
confidence: 94%
“…Significant narrowing of the cervical foramen may present as a sharp arm or neck pain, paresthesia, numbness or tingling sensation with or without symptom spreading to the distal portion of the upper extremities. Motor symptoms such as weakness may accompany sensory symptoms in aggravated cases (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%